REKONSTRUKSI PENAFSIRAN IBNU JARIR AL-THABARI (224–310 H/839–923 M) TENTANG AYAT-AYAT GENDER - Ahmad Mujahid (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article will unravel the thoughts of a classical exegete, namely Ibn Jarir Al-Thabari ( 224–310 H/839–923 AD ) about gender verses. This article refutes some of the claims of feminists that all interpretations of exegetes in the classical era were unfriendly and somewhat negative towards women. This is a qualitative research. The approach used is to follow Amin al-Khuli's approach, namely the ma fi al-Qur'an and ma hawla al-Qur'an approach and also the Schleiermacher approach which emphasizes two important aspects in the process of text interpretation, grammatical interpretation, and psychological interpretation. The conclusion of verse 1 and verse 34 of surah an-Nisa (4) which is the object of discussion is that al-Thabari's interpretation cannot be separated from the patriarchal culture inherent in his time and smells of gender bias. This can be seen when interpreting the nafs wahidah in verse 1 of Surah an-Nisa (4). He understood it as a figure of Adam -sex male. It is different when understanding the concept of qiwamah in verse 34, his opinion is: in line with those understood by contemporary scholars, and this distinguishes him from contemporaries or even after him. He also understands this concept functionally not in a structural form. This refutes the claim among feminists, such as Asma Lambrabet, who generalized that all commentators of the classical period used the concept of qiwamah as a proposition for male superiority even though al-Thabari was different from the others. In addition, he remains faithful in placing this verse in its context, namely only in the domestic sphere, not in the public sphere. Importantly, al-Tabari's paradigm of interpretation which is faithful to history leads him to a more literal understanding of the verse. This is seen when understanding the word dharaba. He understands the meaning with a physical beating, not with metaphorical meaning, even though the beating is light, does not hurt, and does not leave an impression.